Regulating the Financial Cycle: An Integrated Approach with a Leverage Ratio - Dirk Schoenmaker; Peter Wierts (Tinbergen Institute, 2015)
We propose a regulatory approach for restricting debt financing as an amplification mechanism across the financial system. A small stylised model illustrates the trade-off between static and time varying limits on leverage in dampening the financial cycle. The policy section proposes its application to highly leveraged entities and activities across the financial system. Whereas the traditional view on regulation focuses on capital as a buffer against exogenous risks, our approach focuses instead on debt financing, endogenous feedback mechanisms and resource allocation. It explicitly addresses the boundary problem in entity-based financial regulation and provides a motivation for substantially lower levels of leverage and thereby higher capital buffers than in the traditional approach.
Keywords: E58; G10; G18; G20; 330; Financial cycle; macroprudential regulation; financial supervision; (shadow) banking